Development of fatty acid analogues with potent anabolic effects on bone in male mice - Jian-ming Lin; Ivo Dimitrov; Karen E. Callon; Maureen Watson; Ian R. Reid; William A. Denny; Jillian Cornish (Bone Reports)
Natural fatty acids are inhibitory to osteoclastogenesis, but only mildly so, as reported earlier by our and other groups. To improve the potency, we have synthesized two categories of analogues based on the backbone of saturated palmitic acid by inserting an ether or a triazole group in the carbon chain. The most effective compound proved to be with a triazole moiety farthest away from the acid unit. Following this strategy, we now have developed even more potent molecules, methylated triazole and tetrazole analogues. Tetrazole analogue displays about 10-fold higher inhibitory activity over the natural counterpart as tested in the osteoclastogenesis assay using mouse bone marrow cell cultures. Importantly, this inhibition is not due to cytotoxicity as both the methylated triazole and tetrazole molecules slightly increase the viability of bone marrow cells. It was found that the inhibition of osteoclastogenesis by the tetrazole analogue in mouse bone marrow cultures is associated with the decreased expression of the key osteoclastogenic or osteoclastic marker genes: Dcstamp, Nfatc1, Tnfa, Trap and Ctsk. The best analogue-tetrazole was then tested in vivo in a mouse calvarial local injection model after being solubilized by (2-hydroxypropyl)-β-cyclodextrin (β-CD). The results show that the tetrazole at the daily dose of 40 μg/injection (along with 264 μg β-CD) significantly reduce TRAP surface, and significantly increased mineralizing surface/bone surface, mineral apposition rate and bone formation rate. This study provides a novel effective agent for inhibiting osteoclastogenesis and positively regulating bone homeostasis.